Legal Certainty in the Regulation of Intellectual Property Rights in Indonesia - Rosyid Budiyanto; Muhammad Zainuddin; Irfan Rizky Hutomo (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
Intellectual Property Rights (IPR) play a crucial role in fostering innovation and creativity, particularly in the era of rapidly evolving globalization and digitalization. Legal certainty in IPR regulation is crucial in providing fair and effective protection for rights holders and ensuring a balance between individual and societal interests. Indonesia already has various regulations governing IPR, such as the Copyright Law, the Patent Law, and the Trademark Law, which aim to protect the exclusive rights of intellectual property owners. However, in practice, challenges often arise in implementation and enforcement, such as regulatory inconsistencies, weak oversight, and low public awareness of the importance of IPR protection. Therefore, this study aims to analyze legal certainty in IPR regulation in Indonesia by reviewing existing regulatory aspects and the challenges faced in their implementation. This study uses a normative juridical method with a statute approach and a conceptual approach. The study is conducted through an analysis of various national regulations governing IPR and their compliance with the principle of legal certainty. Furthermore, this research also examines the legal principles underlying IPR protection, both nationally and internationally. Using this method, the research is expected to provide a deeper understanding of the extent to which existing regulations contribute to establishing legal certainty for IPR holders and provide recommendations for strengthening legal protection in the intellectual property sector.